Faktor Yang Berhubungan Dengan Kejadian Penyakit Saluran Pernapasan Pada Petani Lada Di Desa Rante Angin - Vera Yuniar; Yuliati; Sumiaty (Pusat Kajian dan Pengelolaan Jurnal FKM UMI, 2026)
Pesticide use in agricultural activities can increase the risk of health problems among farmers, particularly when exposure is repeated and occurs without appropriate Personal Protective Equipment (PPE). One potential health impact is respiratory complaints. This study aimed to identify factors associated with respiratory complaints among pepper farmers in Rante Angin Village, Towuti District, East Luwu Regency. This was an analytical observational study with a cross-sectional design. The study population consisted of all 192 pepper farmers in Rante Angin Village. A total sampling technique was employed, meaning the entire population served as the study sample. Independent variables included pesticide exposure, spraying frequency, duration of employment, and PPE usage, while the dependent variable was respiratory complaints. Data were analyzed using the Chi-Square test at a significance level of α = 0.05. The results showed a significant association between respiratory complaints and pesticide exposure (p=0.021), spraying frequency (p=0.021), duration of employment (p=0.032), and PPE usage (p=0.027) among the pepper farmers. It can be concluded that pesticide exposure, spraying frequency, employment duration, and PPE use are significantly associated with respiratory complaints among pepper farmers in Rante Angin Village.